(untitled) - Mason, Peter (Sydney, 2008)
This book looks at all the key players involved - be they tourists, host communities or industry members - and considers a number of approaches and techniques for managing tourism successfully. Now in a second edition this bestselling text has been fully updated to include updated statistics and case studies, including new cases on tourism planning in Dubai, Antarctic/​Arctic visitor management, wilderness area management in Montana, 7/​7 bombings in the UK and terrorism in Egypt. It also includes new material on governments and planning, the role of tour guides, interpretation, information technology, crisis management and terrorism. Divided into four parts, this text discusses: * The growth, development and impacts of tourism * Tourism planning and management: concepts, issues and key players * Tools and techniques in tourism planning and management: education, regulation and information technology * The future of tourism planning and management: issues of sustainability and the future Up-to-date, international case studies are used to illustrate and provide a real-life context for the theories discussed. Exercises are also included to consolidate learning
Keywords: Tourism,Tourism,Du lịch,Du lịch; Environmental aspects,Social aspects,Khía cạnh môi trường,Khía cạnh xã hội